Life tables of the ladybird beetles Harmonia axyridis, Cycloneda sanguinea and Hippodamia convergens reared on the greenbug Schizaphis graminum - Santos-Cividanes, T. M.; Cividanes, F. J.; Souza, L. S.; Matos, S. T.S. [UNESP]; Ramos, T. O. (FapUNIFESP (SciELO), 2022)
The Asian lady beetle Harmonia axyridis (Coleoptera: Coccinellidae) is a biological control agent that also may adversely impact other coccinellid species. Life table parameters were used to assess the population growth potential and the effects of interspecific competition between the invasive lady beetle H. axyridis and the native coccinellids Hippodamia convergens and Cycloneda sanguinea (Coleoptera: Coccinellidae) under laboratory conditions at 25 °C, using Schizaphis graminum (Hemiptera: Aphididae) as prey. The effects of the abiotic factors air temperature and humidity on these coccinellids by conducting a survey in a sorghum crop under average conditions of 18.1 °C and 53.5%, respectively, were also assessed. Fecundity was higher in C. sanguinea (1021.0 eggs per female) and H. axyridis (1029.2 eggs per female) than in H. convergens (484.5 eggs per female). The majority of the life table parameters showed no significant differences. The instantaneous rates of population increase (rm ) of C. sanguinea, H. axyridis, and H. convergens were 0.195, 0.198, and 0.194 d–1, respectively. Based on the life table parameters obtained in this study, all three species of Coccinellidae showed a similar capacity to control a S. graminum population.
Tabelas de vida das joaninhas Harmonia axyridis, Cycloneda sanguinea e Hippodamia convergens alimentadas com o pulgão-verde Schizaphis graminum
Keywords: aphids; Asian lady beetle; biological control; Coccinellidae; interspecific competition; native species